2010
DOI: 10.1111/j.1439-0531.2009.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LPS on Reproductive System at the Level of the Pituitary of Anestrous Ewes

Abstract: In our research we focused our attention on the effect of the immune stress induced by bacterial endotoxin-lipopolysaccharide (LPS) on the hypothalamic-pituitary-gonadal axis (HPG) at the pituitary level. We examined the effect of intravenous (i.v.) LPS injection on luteinizing hormone (LH) and follicle-stimulating hormone (FSH) release from the anterior pituitary gland (AP) in anestrous ewes. The effect of endotoxin on prolactin and cortisol circulating levels was also determined. We also researched the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 50 publications
4
27
0
1
Order By: Relevance
“…Our study shows the inhibitory effect of LPS-induced immune stress on LH secretion in sheep which is consistent with previous in vivo studies conducted on anestrous ewes [15, 16]. Other researchers also showed that LPS affects LH secretion and even disturbs the preovulatory LH surge in ewes [29, 30].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study shows the inhibitory effect of LPS-induced immune stress on LH secretion in sheep which is consistent with previous in vivo studies conducted on anestrous ewes [15, 16]. Other researchers also showed that LPS affects LH secretion and even disturbs the preovulatory LH surge in ewes [29, 30].…”
Section: Discussionsupporting
confidence: 92%
“…It fully supports the previous studies reported about stimulatory effect of immune stress on cortisol release in various animal species including sheep [2, 16, 20, 43]. The elevation of the cortisol release suggests the activation of the hypothalamic-pituitary-adrenal (HPA) axis, which may result in inhibition of the HPG axis [2, 43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, no effect of either AChE inhibitors or acute immune stress was found upon the circulating concentration of FSH. This also supports the results of previous studies indicating that acute inflammation did not influence the FSH release in both anoestrous [25] and follicular phase ewes [13]. However, other studies on ewes showed that the potency of LPS to affect the secretion of FSH may be dependent upon the duration of the inflammatory stimuli, because prolonged exposition of ewe on the action of bacterial endotoxin was found to disturb FSH release [3, 5].…”
Section: Discussionsupporting
confidence: 89%
“…The stimulatory effect of immune response on the release of cortisol and prolactin has been previously described in sheep [13, 25, 37]. Cortisol is considered as an important inhibitor of the HPG axis activity, targeting the LH release [37].…”
Section: Discussionmentioning
confidence: 99%